The impacts and service responses to injecting cathinones and novel opioids amongst marginalized drug using populations – a scoping review - Scheibein, F.; Wells, J. S. G.; Henriques, S.; Van Hout, M. C. (Journal of Substance Use, 2020)
Background: A growing body of literature reports on the injection of synthetic cathinones (SC) and novel synthetic opioids (NSO) in marginalized drug-using (MDU) populations. This review seeks to establish what is known about the injection of SCs and NSOs impacts on MDUs. Method: A six-stage iterative scoping literature review was conducted in relation to SCs, NSOs, MDU impacts and service responses. Searches were conducted through Pubmed™ and Google Scholar™. Results: Two Thousand and Ninety-Nine search items were retrieved. After duplicates were removed (n = 880), articles were screened for injecting drug use by MDUs leading to the removal of a further 1102 articles. Three articles were identified through a hand search, yielding a total of 22 articles for appraisal. Conclusions: SC injection has largely dissipated in many regions due to service and policy responses and changes in the drug market. Responses to NSO have been less effective, with extensive use and opioid overdosing due to contamination and adulteration within the illicit drug market. These impacts have stimulated innovative responses such as fentanyl test strips and housing-based consumption sites. The evidence for their effectiveness is not established. In this context, the underlying environmental and structural factors shaping the risk of these populations should be addressed.